AN ANALYSIS OF THE EFFECTIVENESS ATTENDANCE ASSESSMENTS ON THE PERFORMANCE OF EMPLOYEES AT KPRI ‘BETIK’ GAWI KOTA BANDAR LAMPUNG - Yugestina Yugestina (Jurnal AKTUAL, 2019)
This study aims to determine the effect of attendance assessments on the performance of employees and administrators at KPRI Betik Gawi Kota Bandar Lampung. This study uses a qualitative analysis approach (used to find out how the relationship of the influence of motivation on employee productivity of the Republic of Indonesia Employee Cooperative) and quantitative analysis (used to determine how much influence the absenteeism assessment on employee performance). Samples in this study used non-probability sampling techniques. Based on the results of the analysis it was concluded that there was a positive influence between the analysis of the effectiveness of attendance assessments on employee performance at KPRI Betik Gawi Kota  Bandar Lampung.